Prophylactic salpingo-oophorectomy in BRCA1 mutation carriers and postoperative incidence of peritoneal and breast cancers - Menkiszak, Janusz (J Ovarian Res, 2016)
BACKGROUND: There are no effective methods of diagnosis of early-stage ovarian cancer. Conservative care over patients at high risk of ovarian and breast cancers is ineffective. Prophylactic surgery is considered the best prophylaxis among BRCA1/BRCA2 carriers. METHODS: One hundred ninety-five patients, carriers of one of three most common mutations of the BRCA1 gene (Am J Hum Genet: 66: (6)1963-1968, 2000) in the Polish population (5382insC, 4153delA and C61G), who undergone prophylactic salpingo-oophorectomy. The study group consisted of consecutive mutation carriers living in Poland, in the West Pomeranian province. Histopathological examination of the surgical material failed to reveal presence of malignancy. RESULTS: During follow-up we diagnosed two peritoneal cancers and 14 breast cancers. Diagnosis of breast cancer before prophylactic surgery increased the risk of peritoneal cancer almost three times. Time from diagnosis of breast cancer to prophylactic surgery increased the risk of peritoneal cancer after prophylactic surgery. This was strongly expressed (HR = 5.0; p = 0.030) in cases of over five-year-long delay in prophylactic surgery. Diagnosis of breast cancer before prophylactic surgery correlated with the risk of death (p = 0.00010). Presence of 5382insC mutation decreased and C61G mutation increased the risk of peritoneal cancer (p = 0.049 vs. p = 0.013). CONCLUSIONS: Occurrence of primary peritoneal cancer after prophylactic surgery is similar to that reported in international literature. Primary breast cancer occurred less often than in international literature. We suspect that the risk of development of breast cancer among BRCA1 carriers undergoing prophylactic surgery can differ in a population. The next goal should be to study the molecular basis for the risk of development of malignancies in any population. Carriers of BRCA1 gene diagnosed with breast cancer should undergo prophylactic surgery within five years from the diagnosis of breast cancer.